Protecting habitats in low-intensity tropical farmland using carbon-based payments for ecosystem services. (28th October 2021) - Davies, Robert W; Morton, Oscar; Lawson, David; Mallord, John W; Nelson, Luke; Boafo, Kwame; Lamb, Ieuan; Edwards, David P
Abstract: Tropical land-use change for agricultural expansion is the primary driver of global biodiversity decline. Efforts to stem this decline often focus on protecting pristine habitats or returning farmland to forest, yet such approaches fail to protect vulnerable taxa reliant on habitats within low-intensity farmland. We assess the economic viability of carbon-based payments for ecosystem services (PES) to protect farmland trees and fallowing in Ghana, which provide vital wintering sites for imperiled Afro-palearctic migrant birds and enhance landscape-level carbon storage. We estimate the carbon breakeven prices (BEPs) associated with alternative agricultural management scenarios that protect existing farmland trees. BEPs associated with tree protection on existing farmland were very low, ranging from US$2.49 to US$6.45 t −1 CO2 . Extending and reintroducing fallow periods also carried competitive BEPs, US$4.67—US$15.45 t −1 CO2, when combined with the protection of 50 trees per hectare. Accounting for leakage and economic uncertainty increased BEPs considerably, but scenarios protecting farmland trees and extending fallow periods remained below EU Emissions Trading Scheme prices. Protecting low-intensity farmland habitats and associated biodiversity is cost-effective under carbon-based PES. Implementation should be combined with efforts to close yield gaps, providing greater local food security and resilience.